Moment-curvature based elasto-plastic model for large deflection of micro-beams under combined loading. (December 2017) - Patel, Bhakti N.; Pandit, D.; Srinivasan, Sivakumar M.
Highlights: A simple explicit elasto-plastic moment-curvature relation is developed. Large deflection of micro-beams under combined load is studied. An incremental method coupled with Runge–Kutta 4th order scheme is used. Springback phenomena is analyzed. Graphical abstract: Abstract: Micro-beams show size dependent structural response which is not predictable from classical beam theories. In this paper, a couple stress theory based analysis of large elasto-plastic deflection of micro-beams is carried out using an incremental moment-curvature constitutive modeling approach. An isotropic hardening model is used for illustration. The developed model is applied to solve the large deflection bending problem of a cantilever under the combined effect of distributed and concentrated load. The solution procedure adopted is based on linearization of the governing differential equation at every load step and subsequently solving the equation by numerical integration. Suitable normalization of the relevant variables have rendered generality. New results pertaining to large elasto-plastic deflections showing evident size-effects are investigated.